Clinical Pharmacology of Pivampicillin - Roholt, K. (1974)
Studies on pivampicillin hydrochloride and ampicillin trihydrate, administered in capsules to healthy volunteers, indicated that pivampicillin was absorbed more efficiently from the gastrointestinal tract than ampicillin. Average peak concentrations of ampicillin in the serum after doses equimolar to 250 mg of ampicillin were 6.8 μg/ml at 56 min with pivampicillin and 1.96 μg/ml at 1 h 24 min with ampicillin. The maximal concentration after pivampicillin treatment was also higher than that recorded when twice the equimolar dose of ampicillin, which averaged 3.2 μg/ml at 1 h 42 min, was used. The urinary excretion of ampicillin, expressed as a percentage of the administered dose, averaged 67 to 73 and 25 to 29% after administration of pivampicillin and ampicillin, respectively. The bioavailability of ampicillin, taken as the area under the serum curve, obtained with pivampicillin at a 250-mg ampicillin dose level was superior to that obtained with a 500-mg dose of ampicillin. Comparison of a suspension intended for children, containing the pivampicillin free base with a suspension of ampicillin trihydrate, emphasized the difference recorded for the capsule preparations. Administration of pivampicillin with a meal rich in fat and protein had no depressant effect on the absorption. Concurrent administration of probenecid caused higher and prolonged concentrations of ampicillin in the serum.